Mapping Future Research Employee Fraud with Bibliometric Analysis - Farlina Wahyulistyo; Nur Cahyonowati (Jurnal ASET (Akuntansi Riset), 2022)
This study aims to present and explain employee fraud by reviewing bibliometric analysis gathered from the Scopus database from 2011 until 2020. The analysis method uses the VOSviewer application system for data visualization and Microsoft Excel to perform data frequency analysis. The results indicate that there is still a lack of research on employee fraud from 2011 until 2020. Meanwhile, it contradicts the results of the ACFE survey which shows a shifting in the trend of fraud perpetrators. For instance, in 2019 the first place was occupied by directors/owners, while in 2020 fraud perpetrators were dominated by employees. Hopefully, this research helps encourage other researchers to conduct research on employee fraud in the field of detection and prevention for the sake of the sustainability of an organization. To the best of the author's knowledge, a bibliometric analysis study of employee fraud using the Scopus database is difficult to find